Multinational corporations' politics and resistance to plant shutdowns: A comparative case study in the south of France. (March 2013) - Contu, Alessia; Palpacuer, Florence; Balas, Nicolas
MNCs' politics has been considered a 'contested terrain' and further research is needed into the dynamics between the Head Office's drastic restructuring decisions and local responses to understand how collective resistance is performed, and on what conditions. A neo-Gramscian approach is developed to analyse two plants in France facing drastic restructuring, including shutdown. We trace the dynamics of forces significant in aligning resisting subjects. We identify two structural processes – chains of equivalence and chains of difference – which were significant to the constitution of resistance. This article contributes to the development and refinement of a neo-Gramscian approach to management and organization studies in general and to multinational corporations' politics in particular. It refines the study of multinational corporations' politics by explaining how collective resistance is constituted and organized, what favours and limits the possibility of creating a collective antagonistic front and the role of local managerial resistance.